2020
DOI: 10.26434/chemrxiv.13120139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlating Experiment and Theory for Electron Paramagnetic Resonance and Substrate Binding in a Lytic Polysaccharide Monooxygenase

Abstract: <div>Lytic polysaccharide monooxygenases (LPMOs) are enzymes that binds polysaccharides followed by an (oxidative) disruption of the polysaccharide surface, thereby boosting depolymerization. The binding process between LPMO and polysaccharide is key to the mechanism and recent investigations have established structure-function relationships for this binding, employing hyperfine coupling constants (HFCs) from EPR spectroscopy. Unfortunately, EPR does not provide direct structural data and therefore the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…S15). The reduction in distance between Tyr-O and Cu is also reproduced qualitatively in the QM/MM-optimized structures of LsAA9_A, where the distance was found to decrease by 0.2-0.3 A ˚upon LsAA9_A binding the substrate (Theibich et al, 2021). While the role of tyrosine remains unclear, the shortening of the Tyr-O to Cu bond has been shown here to be reproducible for LsAA9_A.…”
Section: Photoreduction Of Lsaa9_a Crystals Soaked With Oligosaccharidessupporting
confidence: 68%
See 2 more Smart Citations
“…S15). The reduction in distance between Tyr-O and Cu is also reproduced qualitatively in the QM/MM-optimized structures of LsAA9_A, where the distance was found to decrease by 0.2-0.3 A ˚upon LsAA9_A binding the substrate (Theibich et al, 2021). While the role of tyrosine remains unclear, the shortening of the Tyr-O to Cu bond has been shown here to be reproducible for LsAA9_A.…”
Section: Photoreduction Of Lsaa9_a Crystals Soaked With Oligosaccharidessupporting
confidence: 68%
“…In the lowest-dose substrate-free structures of fungal/bacterial LsAA9_A, the distance to the equatorial water ligand is in the range 2.2-2.3 A ˚, while that to the axial ligand is in the range 2.6-2.7 A ˚. For comparison, QM/MM models have shown distances of 2.16/2.25, 2.08/2.53 and 2.21/2.34 A ˚for the equatorial/axial water molecule, depending on the parameters of the calculation (Theibich et al, 2021), which could indicate that even at the lowest X-ray dose possible, a small amount of photoreduction has occurred.…”
Section: Photoreduction Of Substrate-free Aa9smentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the axial water displacement upon substrate binding seen in crystallographic work [27] was confirmed (along with other modifications of the active site) since it was reflected in the obtained spin‐Hamiltonian parameters [27,42,105] . In recent papers, calculated spin‐Hamiltonian parameters were compared with the experimental ones [74,100,106,107] . A qualitative agreement was achieved, but the EPR parameters are infamous for being very dependent on the computational setup.…”
Section: An Overview Of the Substrate Oxidation Mechanismmentioning
confidence: 72%
“…This can be compared to the QM‐cluster and QM/MM structure optimizations, which show that the reduction is associated with dissociation of the equatorial water molecule [66,71] . A recent paper by Theibich et al [100] . compared QM/MM and X‐ray structures, which showed that QM/MM qualitatively reproduces changes induced by substrate binding (unfortunately, no RMSD values were reported).…”
Section: An Overview Of the Substrate Oxidation Mechanismmentioning
confidence: 99%